Peci Tensi: Public education efforts on the dangers of hypertension in Cipayung Urban Village, West Java - Dyah Utari; Fandita Tonyka Maharani; Azizah Musliha Fitri (Community Empowerment, 2022)
Hypertension is a dangerous degenerative disease that is often asymptomatic, so it is dubbed the silent killer. Increasing public knowledge about the dangers of hypertension is the key to controlling this disease. The purpose of this community service activity is to increase people's knowledge about the dangers and efforts to prevent hypertension. The activity was carried out by providing counseling, cardiac exercise, and checking the participants' blood pressure. The result of this activity is an increase in public knowledge and commitment to take steps to prevent hypertension through efforts to change a healthier lifestyle. It is hoped that this activity can be carried out continuously by cadres and residents of Cipayung Urban Village.